(untitled) (Modern education and development, 2025)
Female germ cells are called eggs, and male germ cells are called spermatozoa. Both of them are involved in fertilization. The egg matures every month in the left or right ovary, and then leaves it to meet the male sex cell. Let’s take a closer look at the structure of the egg in order to learn more about the processes that take place inside us.